Penerapan Model Inkuiri Terbimbing untuk Meningkatkan Literasi Sains Siswa dalam Pembelajaran IPA Biologi - Yefita Aprizanti (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
The implementation of learning in junior high school has been using a teacher-centered approach and a non-variative learning model. Students were actively involved in seeking knowledge on their own and still get information from the teacher, so they are less creative. This study was aimed at determining the improvement in students’ scientific literacy in biology by using guided inquiry models. This research used a qualitative approach with the form of classroom action research. The data sources were 20 students of class 9 B in SMPN 2 Ujan Mas, at the 2020/2021 academic year. Data were collected through tests, observations, interviews, and field notes. The result showed the application of learning using a guided inquiry model can improve students’ scientific literacy in the chapter of the plant development system. The result of the last test in the first cycle was 45% and increase on the second cycle to 85%. The activity of teacher and students on the learning process was a good category and the student was actively involved in the learning process. The conclusion is the guided inquiry models could improve students’ scientific literacy on the subject of biology.